Analisis Kekuatan Tarik dan Regangan Filamen Carbon Fiber Hasil 3D Print dengan Variasi Fill Density - Braam Delfian Prihadianto; Suryo Darmo; Dani Anggoro Hasan; Dovan Ndaru Ananda (P3M Politeknik Negeri Cilacap, 2023)
Mechanical properties problems that are closely related to the strength of 3D printed products generally occur during the development of 3D printing machines, In which several components used are the results of additive manufacturing technology. The damages generally occur in the components that receive force and the damage is in the form of cracks and fractures. The focus of this study is to determine the effects of increasing the value of fill density on mechanical properties, especially tensile strength and strain with carbon fiber filament material. This study used an experimental method using two types of filament material: nylon carbon fiber and PLA carbon fiber with a diameter of 1.75 mm for each filament and a recommended printing temperature of 190-260°C. Both types of filaments were printed using a direct extruder type 3D printing machine with a build size of 180 mm x 180 mm x 180 mm and printing was carried out at atmospheric pressure and a horizontal printing area. The Universal Testing Machine carried out mechanical properties testing implementation related to tensile strength and strain. Based on the results of experiments and tests that have been carried out, the strain values ​​are 16.970 – 26.681% and the tensile strength is 19.244 – 23.899 MPa for nylon carbon fiber filament material. Whereas the PLA carbon fiber filament material, the strain value is 7.673 – 15.546%, and the tensile strength is 18.580 – 24.552 MPa. Therefore, based on the test results, it is known that the fill density parameter value has an influence on the strain value and tensile strength so that it can be used as a reference in setting machining parameters.